2000
DOI: 10.1034/j.1600-0889.2000.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the ACE-2 CLOUDYCOLUMN closure experiment

Abstract: International audienceCLOUDYCOLUMN is one of the 6 ACE-2 projects which took place in June-July 1997, between Portugal and the Canary Islands. It was specifically dedicated to the study of changes of cloud radiative properties resulting from changes in the properties of those aerosols which act as cloud condensation nuclei. This process is also refered to as the aerosol indirect effect on climate. CLOUDYCOLUMN is focused on the contribution of stratocumulus clouds to that process. In addition to the basic aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 3 publications
1
72
0
Order By: Relevance
“…The most extensive observations were conducted close to local noon (Brenguier et al, 2000a(Brenguier et al, , 2000bSnider et al, 2000;. The flight time, on 26 June was from 11:50 LST to 14:50 LST, while on 9 July, it was from 12:40 LST to 15:50 LST, and, our comparisons were conducted at the corresponding flight time.…”
Section: Base Case Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most extensive observations were conducted close to local noon (Brenguier et al, 2000a(Brenguier et al, , 2000bSnider et al, 2000;. The flight time, on 26 June was from 11:50 LST to 14:50 LST, while on 9 July, it was from 12:40 LST to 15:50 LST, and, our comparisons were conducted at the corresponding flight time.…”
Section: Base Case Resultsmentioning
confidence: 99%
“…The second Aerosol Characterization Experiment (ACE-2), was promoted by the International Global Atmospheric Chemistry project ; and was carried out from 16 June to 24 July 1997 between Portugal, the Azores, and the Canary Islands (29.4 N, 16.7 W). The CLOUDY-COLUMN (CC) experiment, one of the six field projects during ACE-2, aimed to examine aerosol effects on the microphysical and radiative properties of marine boundary layer clouds (Brenguier et al, 2000a. Previous observations showed that the clean marine air over this area often alternates with the anthropogenic pollution originating from Europe and North Africa, and this alternation was also observed during ACE-2 (Verver et al, 2000).…”
mentioning
confidence: 99%
“…Ship tracks observed from satellite (Coakley et al, 1987;Durkee et al, 2000, and the paper series of the MAST special issue therein) provided the first evidence of cloud microphysical impacts on cloud radiative properties. The CLOUDY-COLUMN experiment during ACE-2 (Raes et al, 2000) was specifically designed as a column closure experiment between aerosol, cloud microphysics and cloud radiative properties in marine stratocumulus clouds, North of the Canary Islands (Brenguier et al, 2000a). In situ measurements of aerosol, cloud condensation nuclei (CCN) and cloud microphysics combined with independent remote sensing measurements of cloud radiative properties from above the cloud layer corroborated the expected relationships between CCN concentration, cloud droplet number concentration (CDNC) and cloud optical thickness (Brenguier et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the optical thickness is linked to geometrical thickness, if the droplet size distribution or the according effective droplet radius is known. The latter is estimated from the LWC using fixed cloud droplet densities taken from publications on the ACE2 CLOUDYCOLUMN campaign [Brenguier et al, 2000b;Chuang, 2000]. Mean scene cloud properties are derived by averaging all values of cloudy pixels.…”
Section: Independent Pixel Retrievalmentioning
confidence: 99%
“…All scenes are of similar size of about 1.3 km  10 km. Some auxiliary information (in situ measurements of number densities of droplets or cloud condensation nuclei) is taken from publications on the ACE2 CLOUDYCOLUMN campaign [Brenguier et al, 2000b;Chuang, 2000].…”
Section: Datamentioning
confidence: 99%